IMPLEMENTASI MANAJEMEN SARANA DAN PRASARANA BERBASIS MULTIPLE INTELLIGENCE DI TAMAN KANAK-KANAK ALAM AR RAYYAN - Alfiantono, Eka Rizky Cahya (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
ABSTRACT Facilities and infrastructure management is one of the management concepts under the auspices of Early Childhood Education (PAUD) institutions. Multiple intelligence-based schools are a development pattern in which the media provided to students is not only a fulfillment of intellectual intelligence stimulation but each student is able to form and develop other intelligences in each of their activities. his activities. In the continuity of learning, multiple intelligence becomes a reference for continuity of planning and procurement of school facilities and infrastructure. There is implementation of infrastructure in multiple intelligence-based schools in the form of structured development of student abilities by providing school infrastructure. The focus of this research is: 1) What forms of multiple intelligence are implemented in the management of facilities and infrastructure at Alam Ar Rayyan Kindergarten? 2) How is the implementation of multiple intelligence-based facilities and infrastructure management at Alam Ar Rayyan Kindergarten? Keywords: 1. Management, 2. Infrastructure, 3. Multiple Intelligence ABSTRAK Manajemen sarana dan prasarana merupakan salah satu konsep manajemen yang ada dibawah naungan institusi Pendidikan Anak Usia Dini (PAUD). Sekolah berbasis multiple intelligence merupakan pola pengembangan bahwa media yang diberikan kepada peserta didik tidak hanya sebagai pemenuhan rangsangan kecerdasan intelektutal tetapi setiap peserta didik mampu terbentuk dan berkembang kecerdasan yang lain di setiap aktivitasnya. aktivitasnya. Dalam keberlangsungan pembelajaran, multiple intelligence menjadi acuan keberlangsungan perencanaan hingga pengadaan sarana dan prasarana sekolah. Adanya implementasi sarpras pada sekolah berbasis multiple intelligence berupa pengembangan kemampuan peserta didik yang terstruktur dengan pengadaan sarpras sekolah. Fokus penelitian ini adalah : 1) Apa saja bentuk multiple intelligence yang di implementasikan dalam manajemen sarana dan prasarana di TK Alam Ar Rayyan? 2) Bagaimana implementasi manajemen sarana dan prasarana berbasis multiple intelligence di TK Alam Ar Rayyan?. Kata-Kata Kunci: 1. Manajemen, 2. Sarana Prasarana, 3. Multiple Intelligence